Criminalization : Politics and Policies - Balyan, Chirag,; Pal, Garima, (Social Sciences E-Books Online, Collection 2025., 2025)
Criminalization: Politics and Policies provides a thorough analysis of the relationship between politics, policies, and criminalization. Through diverse perspectives and scholarly essays, it explores the multifaceted issues in criminal justice, law, and governance. The book scrutinizes the impact of law, society, politics, and penal populism on criminalization across legal systems, advocating for a reassessment of criminal law's scope. It delves into the prevalence of resorting to criminalization for social issues, urging for a critical review. Additionally, it examines the normative foundations of criminalization, addressing 'over'-criminalization and exploring its empirical and normative aspects. The anthology also considers the roles of prosecutorial and judicial discretion, as well as State preventive powers, in over-criminalization. Whether a scholar, policymaker, or citizen, readers gain insights into the expansion of criminal laws and their consequences, making it a valuable resource for understanding the dynamics of law, politics, and power in criminal justice. Contributors are Naveed Ahmad, Chirag Balyan, Shruti Bedi, Subhangi Jain, Charles Khamala, Sébastien Lafrance, Sidharth Luthra, David McCallum, Garima Pal, Daria Ponomareva, Alok Prasanna, Yogesh Pratap Singh, and Ekkehard Strauss.